PENGEMBANGAN INTERNET SIMULATOR BERBASIS OFFLINE PADA SMP DI KABUPATEN KEPULAUAN SELAYAR - Abdul Ma'arief Al Imran; Yunus Tjandi; Purnamawati (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2021)
This study aims to: a) find out the results of the steps for developing an offline-based internet simulator in junior high schools in the Selayar Islands Regency, and b) find out whether the development of an offline-based internet simulator is valid, practical and effective for use in junior high schools in the Selayar Islands Regency. The method used in this research is Research and Development (R&D). The development stages used refer to the waterfall development model which consists of five steps, namely:a) requirements analysis and definition, b) system and software design, c) implementation and unit testing, d) system integration and testing, and e) operations and maintenance. The results of the study: a) At the stage of needs analysis and definition, needs analysis and curriculum analysis were carried out. Needs analysis is done by means of observation and interviews with subject teachers, and curriculum analysis is done by analyzing the applicable curriculum. b) At the system and software design stage, it is determined the content that will be provided on the product to be developed, and the product design is made in the form of a diagram. c) At the stage of implementation and unit testing, the software is made based on the software design that has been made previously. At this stage, testing the functions contained in the software by expert validators is also carried out. d) At the stage of integration and system testing, limited testing is carried out and improvements are made to the software in accordance with the results of the limited trial. e) At the operation and maintenance stage, field testing is carried out and improvements are made based on the results of field trials. The results of validity testing conducted by 2 expert validators indicate that the software developed is included in the very valid category. The results of small group trials indicate the level of practicality of the software developed is included in the practical category, while the level of effectiveness of the software developed is included in the effective category. The results of field trials indicate that the level of practicality of the software developed is included in the practical category, while the level of effectiveness of the software developed is included in the effective category